ANALISIS PENGARUH INFLASI, EKSPOR, DAN PENGANGGURAN TERHADAP PERTUMBUHAN EKONOMI - Natasya; Saputra, Putu Mahardika Adi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The purpose of this study is to determine the effect of inflation, exports, and unemployment on economic growth in 5 ASEAN countries in 1991-2020. Using the panel data regression analysis method, this study found that inflation, exports and unemployment had a significant effect on economic growth in 5 ASEAN Countries. This research is in line with several previous studies, namely by Jean and Mahardika (2013); Fathoni et al (2017), and Panigrahi et al (2020).